2012
DOI: 10.1002/gps.3797
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane review on ‘Statins for the treatment of dementia’

Abstract: There is insufficient evidence to recommend statins for the treatment of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 79 publications
1
45
0
Order By: Relevance
“…Whereas the psychometric changes in the placebo arm are in keeping with observed changes reported elsewhere in similar populations, 28,29 the change in ADAS-cog was double than anticipated. 4 While every attempt was made to improve internal validity by ensuring raters received the same psychometric rating training and, wherever possible, not change between visits, small numbers in the study cannot rule out the random allocation of a more rapidly declining group to the placebo arm and differences between groups should be viewed with caution.…”
Section: (1) 4 (3)supporting
confidence: 72%
“…Whereas the psychometric changes in the placebo arm are in keeping with observed changes reported elsewhere in similar populations, 28,29 the change in ADAS-cog was double than anticipated. 4 While every attempt was made to improve internal validity by ensuring raters received the same psychometric rating training and, wherever possible, not change between visits, small numbers in the study cannot rule out the random allocation of a more rapidly declining group to the placebo arm and differences between groups should be viewed with caution.…”
Section: (1) 4 (3)supporting
confidence: 72%
“…Since 2012, systematic reviews [5,[29][30][31] and narrative reviews [32][33][34][35] have repeatedly reported a lack of conclusive evidence that statins cause cognitive impairment. A Cochrane review in 2013 found that a mean reduction in LDL-C by 22 % was not associated with worsening of cognitive function [36].…”
Section: The Statin Experiencementioning
confidence: 99%
“…There is also evidence of a mechanism for reduction of cholesterol levels in the brain that leads to reduction of NFTs and some pleiotropic effects attributed to anti-inflammatory properties. 20,45 Use of statins may be an important adjunct in treating AD. Some physicians have advocated their use as a preventive measure for patients who have a dementia risk profile mediated by cerebral vasculature.…”
Section: Tamibarotenementioning
confidence: 99%
“…Furthermore, it needs to be borne in mind that statins have a risky safety profile and there may be hepatic impairment and risk of rhabdomyolysis at doses that would be effective for continuous treatment of AD. 18,20 In a meta-analysis on separately evaluated cross-sectional and longitudinal observational studies (total of 19), the crosssectional studies showed that statins had a protective effect, and it was noted that use of statins was associated with a reduced risk of developing AD and other forms of dementia. However, progress in such studies is still restricted by bias in some of them.…”
Section: Tamibarotenementioning
confidence: 99%
See 1 more Smart Citation